A content analysis of Environmental Science I - Galvante, Wulfilda P. (s.n.], 1974)
This study determined the index of student involvement and word loading of the textbook, Environmental Science I. It measured the student involvement of the book in terms of: (1) the text; (2) the figures, diagrams, and illustrations in the text; and (3) the activities required of students. It also identified the unfamiliar technical and non-technical terms used in the textbook.